THE PROBLEM OF THE EXECUTION OF CHILD CUSTODY (HADANAH) DECISION BY THE RELIGIOUS COURTS IN INDONESIA - Prihatini, Farida; Munthe, Abdul Karim; Pusparani, Delila Stefanya; Sumihar, Ali (Jurnal Syariah, 2019)
This article analyses the problems in the execution of child custody decision by Religious Courts in Indonesia. The implementation of court decisions reflects the court’s dignity. However, the victory over child custody decision issued by the Court sometimes only the formality on the paper. Sometimes, the implementation of the court decision is hindered if there is no willingness from the involved parties. This research uses normative legal research method with conceptual approach and field research. This research found that the implementation of child custody decision is prevented by the quality of verdict, inadequate rule of execution, and the norm which woman is perceived as the better party to hold child custody rights. In addition, the execution of child custody decision cannot be adequately implemented using Het Herziene Indonesisch Reglement (HIR) solely, but it needs new regulation to accommodate the child interest, lawfully and psychologically.